Peculiarities of Atypical Meningiomas: Literature Review - Santos, Rafael Rodrigues Pinheiro dos; Rampazzo, Ana Carla Mondek; Zicarelli, Carlos Alexandre Martins; Camargo, Leonardo Valente de (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Meningiomas are common tumors of the central nervous system that represent around 30% of primary tumors. However, the incidence of atypical meningiomas (AMs) is lower, of approximately 15% of all meningiomas, and they present high rates of relapse and mortality.Aim To review peculiarities of AMs.Methodology A literature review of articles published in English between 2009 and 2020 on the PubMed and Biblioteca Virtual em Saúde (BVS) databases using the terms meningioma and atypical.Results Atypical meningiomas are rare and more prevalent in older males. The clinical condition depends on the site of the tumor, and a definitive diagnosis of AM is only possible via anatomical pathology. Moreover, prominent studies have indicated a relationship between the presence of the anti-Ki67 antibody/mindbomb (Ki-67/MIB1) marker as an aid in the definition of AM and one of the determinants of tumor aggressiveness. Imaging studies have also advanced in terms of seeking criteria using magnetic resonance that may suggest the malignancy of a lesion. As far as treatment is concerned, total resection remains the main therapeutic option, and it has a direct relationship with survival and time until disease progression. Lastly, there are many factors involved in the prognosis of AM.Conclusion Atypical meningiomas continue to be a challenge, requiring further and more specific studies to provide a better understanding of it.
Keywords: meningioma; malign meningioma; immunohistochemistry; prognosis